Deteksi dan Pengukuran Spektra dalam Analisis Spektrografi Emisi dengan Pengolahan Citra - Itmy Hidayat Kurniawan; Sahat Simbolon (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
Qualitative and quantitative analysis on emission spectrograph detector are important to identify impurities elements in nuclear fuel. the process is still using a densitometer based manual method which has limitations due mechanical factors on instrument and expert chemists requirements. To reduce measurement error on manual methods, we develops analytical methods by processing scanned digital image of a spectrogram. The aim of this paper is to identify impurities on nuclear fuel elements (boron and cadmium in uranium oxide). Image processing is done by cropping digital image to separate each the spectra result of excitation processes and identify impurities, which enlarged later to refine the distribution of signal intensity of pixels. Signal processing methods for quantitative analysis conducted with pulse peaks analysis. Results obtained then substituted into a standard curve obtained from regression analysis of sample reference to calculate concentration of the element. End results indicated that signal processing can be used to identify and analyze the elements in the detector, element concentrations value of image processing is not different from the results of analysis of densitometer on statistic significancy level of 5%.